Embodiment and Agency - Sherwin, Susan, 1947-; Meynell, Letitia; Campbell, Sue, 1956- (Book collections on Project MUSE., 2009)
"A collection of essays in feminist philosophy. Contributors theorize how we act through differently acculturated bodies in a variety of interpersonal and political contexts. Addresses recent feminist challenges to bring the body more fully and positively into theory"--Provided by publisher